2010
DOI: 10.1177/000348941011901208
|View full text |Cite
|
Sign up to set email alerts
|

Angioedema: A Review of 367 Episodes Presenting to Three Tertiary Care Hospitals

Abstract: The novel findings of this study are lower rates of airway intervention than reported previously and the fact that multiple affected sites were associated with admission and intubation or tracheostomy, particularly when the edema involved the larynx or hypopharynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 19 publications
6
43
0
2
Order By: Relevance
“…5,6 Our main goal was to identify possible risk factors for a severe reaction leading to hospitalization. Several factors were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Our main goal was to identify possible risk factors for a severe reaction leading to hospitalization. Several factors were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Other well-designed studies showed an incidence of 0.2-2.5% (13)(14)(15). Among patients presenting to a hospital with acute angioedema, 39-46% were treated with ACEi (5,16). In a specialised out-patient setting the incidence was found to be 11% (17).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 94%
“…1) (17). A lump in the throat, drooling, stridor and a hoarse voice or aphonia are possible symptoms, when the airways are involved, signalling a severe situation with the need to act immediately and secure the airway (16,22). Abdominal pain might be a rare and sometimes the only sign of ACEi-induced angioedema, since the swellings can be present solely in the abdominal organs, most often the intestines (29,30).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Although the swelling can affect any part of the body, it has a predilection for areas with loose connective tissue, including the face (especially the lips, tongue and periorbital area), pharynx, larynx, abdomen, genitalia and extremities [11,12,13]. The swellings manifest as recurrent episodes of pronounced localized edema with ill-defined margins.…”
Section: Resultsmentioning
confidence: 99%